2016
DOI: 10.3390/molecules21070873
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Nor-β-lapachone by PLGA Microparticles: A Strategy for Improving Cytotoxicity against Prostate Cancer Cells

Abstract: Prostate cancer is one of the most common malignant tumors in males and it has become a major worldwide public health problem. This study characterizes the encapsulation of Nor-β-lapachone (NβL) in poly(D,L-lactide-co-glycolide) (PLGA) microcapsules and evaluates the cytotoxicity of the resulting drug-loaded system against metastatic prostate cancer cells. The microcapsules presented appropriate morphological features and the presence of drug molecules in the microcapsules was confirmed by different methods. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…From the in vitro drug release experiment, it is clearly shown that LTZ can gradually be released from the microparticles in a sustained fashion for 30 days, while the free LTZ reached the concentration plateau in 12 to 24 h. The sustained cytotoxicity of drug-loaded microparticles could be additionally attributed to the internalization of LTZloaded MDP into the cells and the successive drug release from microparticles inside the cells, enhancing the action of LTZ and preventing the short acute action of the drug. Similar findings regarding the uptake of Nor--lapachone-and Doxorubicin-PLGA loaded microparticles by treated cancer cells were previously reported [57,58,59]. Our results also indicated that our formulations were non-toxic to MEC normal breast epithelial cells at all concentrations expect for 100 µM, which indicates that these monodisperse polymeric formulations manufactured using the VOAG technology are potentially safe to noncancerous cells (Figure 9).…”
Section: In Vitro Cytotoxicity Studiessupporting
confidence: 90%
“…From the in vitro drug release experiment, it is clearly shown that LTZ can gradually be released from the microparticles in a sustained fashion for 30 days, while the free LTZ reached the concentration plateau in 12 to 24 h. The sustained cytotoxicity of drug-loaded microparticles could be additionally attributed to the internalization of LTZloaded MDP into the cells and the successive drug release from microparticles inside the cells, enhancing the action of LTZ and preventing the short acute action of the drug. Similar findings regarding the uptake of Nor--lapachone-and Doxorubicin-PLGA loaded microparticles by treated cancer cells were previously reported [57,58,59]. Our results also indicated that our formulations were non-toxic to MEC normal breast epithelial cells at all concentrations expect for 100 µM, which indicates that these monodisperse polymeric formulations manufactured using the VOAG technology are potentially safe to noncancerous cells (Figure 9).…”
Section: In Vitro Cytotoxicity Studiessupporting
confidence: 90%
“…The reaction of 1 with aldehyde derivatives and 3‐substituted isoxazol‐5‐amine under microwave irradiation within short periods of 10–26 min in acetic acid yielded benzo[h]isoxazolo[5,4‐b]quinolin‐5,6‐dione derivatives 305 in yield 61–91% . Refluxing 1 with aromatic amine and aromatic aldehyde in the presence of indium(III) chloride (InCl 3 ) for 5.5–7 h or stirring at r.t. for 5 h afforded 2‐(arylr(arylamino)methyl)naphthalene‐1,4‐dione 306 in yield 70–91% (Scheme ).…”
Section: Reactivity Of Lawsonementioning
confidence: 99%
“…Lawsonia alba Lam. ( L. alba ; HNQ) is locally known as henna or mehndi . HNQ was showed the presence of keto‐enol form that may be suitable for electrochemical receptor for anions such as CN − , AcO − , F − , and H 2 PO 4 − ions (Fig.…”
Section: Introduction and Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Beta-lapachone (bL) is an o-naphthoquinone extracted from plants and has many pharmacological effects [14]. In the last decade, many studies to elucidate the effect of bL on cancer development have been conducted and have shown that bL has an inhibitory effect on various cancers such as epidermoid laryngeal cancer [15] and prostate [16][17][18][19], colon [20,21], ovarian [19], lung [22], and breast cancer [23]. bL has been identified to suppress cancer proliferation by directly interacting with and inhibiting the catalytic activity of DNA topoisomerase I [24], by inducing apoptosis or necrosis by releasing mitochondrial cytochrome C from mitochondria [25] and PARP cleavage [26,27], by blocking the lethal DNA damage repair (PLDR) system [28], by inducing G1/S cell cycle arrest [29], and by activating c-JUN NH2-terminal kinase [30] and caspases [31].…”
Section: Introductionmentioning
confidence: 99%